(untitled) (Journal of Engineering, 2024)
This research utilized natural asphalt (NA) deposits from sulfur springs in western Iraq. Laboratory tests were conducted to evaluate the performance of an asphalt mixture incorporating NA and verify its suitability for local pavement applications. To achieve this, a combination of two types of NA, namely soft SNA and hard HNA, was blended to create a binder known as Type HSNA. The resulting HSNA exhibited a penetration grade that adhered to Iraqi specifications. Various percentages of NA (20%, 40%, 60%, and 80%) were added to petroleum asphalt. The findings revealed enhanced physical properties of HSNA, which also satisfied the requirements outlined in the Iraqi specifications for asphalt cement. Consequently, HSNA can serve as an asphalt binder to produce asphalt mixtures for flexible paving construction. Notably, HSNA mixtures exhibited greater Marshall stability and stiffness index when compared to traditional mixtures. The results from indirect tensile strength (ITS) and tensile strength ratio (TSR) tests indicated that the 80NA mixture displayed the highest ITS values and a TSR of 81.36%, surpassing the TSR of the mixture incorporating petroleum asphalt by 0.57%.